2023
DOI: 10.3390/vaccines11030614
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoint Inhibitors in HBV-Caused Hepatocellular Carcinoma Therapy

Abstract: Hepatitis B virus (HBV) infection is the main risk factor for the development of hepatocellular carcinoma (HCC), the most common type of liver cancer, with high incidence and mortality worldwide. Surgery, liver transplantation, and ablation therapies have been used to treat early HBV-caused HCC (HBV-HCC); meanwhile, in the advanced stage, chemoradiotherapy and drug-targeted therapy are regularly considered, but with limited efficacy. Recently, immunotherapies, such as tumor vaccine therapy, adoptive cell trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 145 publications
0
7
0
Order By: Relevance
“…Inhibition of the activity of immunological checkpoint molecules can prevent the negative HAIC-Len-PD1 in TACE-refractory HCC regulation of the immune response, enhance the capacity of immune cells to eradicate tumor cells, and control the growth of malignancies. 36 Additionally, immunity activation was further enhanced in triple combination therapy, thus providing more benefits for HBsAg-positive individuals. Subgroup analyses of OS demonstrated that patients who had just two sessions of TACE could benefit more from the triple therapy than those with over two procedures of TACE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of the activity of immunological checkpoint molecules can prevent the negative HAIC-Len-PD1 in TACE-refractory HCC regulation of the immune response, enhance the capacity of immune cells to eradicate tumor cells, and control the growth of malignancies. 36 Additionally, immunity activation was further enhanced in triple combination therapy, thus providing more benefits for HBsAg-positive individuals. Subgroup analyses of OS demonstrated that patients who had just two sessions of TACE could benefit more from the triple therapy than those with over two procedures of TACE.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HBsAg‐positive patients benefited more from tri‐combination treatment while HBsAg‐negative patients were less sensitive to tri‐combination therapy. Inhibition of the activity of immunological checkpoint molecules can prevent the negative regulation of the immune response, enhance the capacity of immune cells to eradicate tumor cells, and control the growth of malignancies 36 . Additionally, immunity activation was further enhanced in triple combination therapy, thus providing more benefits for HBsAg‐positive individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, an immunebased strategy may be more widely applicable, as immune evasion is a universal phenomenon in cancers. Immune prevention has shown success in cancers associated with infectious agents such as hepatitis B 47 and human papillomavirus 48 . However, applying lung cancer immune prevention faces challenges due to our limited understanding of the evolving interplay between premalignant/malignant cells and the host's anti-tumor immunity during the formation and progression of pre-cancerous lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Bridging procedures such as transcatheter arterial chemoembolization and selective internal radiotherapy have been able to further improve oncological outcomes in patients with HCC, and new therapeutic approaches such as immunotherapy have been established [ 5 , 6 , 7 , 8 , 9 , 10 ]. Even if immune checkpoint inhibition is currently not implemented in the bridging of patients with HCC on the waiting list, it is encouraging that this approach has the potential to further improve bridging therapy in combination with conventional bridging methods [ 8 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%